THE CONTRIBUTION OF NETIZENS TO FLASH FLOOD JOURNALISM IN SUMATRA THROUGH THE INSTAGRAM ACCOUNT @kitabisacom - Tria Pratiwi; M. Yoserizal Saragih (Program Pascasarjana UIN Sumatera Utara, 2026)
The flash floods in Sumatra in 2025 not only presented a humanitarian crisis but also demonstrated the strengthening of participatory journalism practices on social media. This study aims to analyze netizens' contributions to disaster journalism through the Instagram account @kitabisacom, while explaining how these contributions are framed into narratives of humanity and digital solidarity. The study uses a constructivist paradigm with a descriptive qualitative approach and Robert N. Entman's framing analysis. Data were obtained from netizens' posts, captions, and comments on content related to the flash floods, then tested through triangulation of sources and theories. The results show that @kitabisacom consistently framed the floods as an urgent humanitarian crisis by highlighting the conditions of victims, volunteer activities, and the urgency of aid. Netizens are not present merely as audiences, but as contributors of information, reinforcers of meaning, and drivers of digital solidarity through comments, message distribution, and donation support. The novelty of this study lies in explaining how the contributions of digital citizens curated by philanthropic platforms shape the construction of collective meaning in disaster journalism on Instagram. These findings confirm that social media functions not only as an information channel, but also as a space for mobilizing empathy and collective action in disaster situations.